Utilization of RFLP in V-Model methodology for the interdisciplinary development of Digital Twins - Fett, Michel; Wilking, Fabian; Götz, Stefan; Wartzack, Sandro; Kirchner, Eckhard (Forschung Im Ingenieurwesen-Engineering Research, 2025)
Digital Twins have numerous potentials like performance analysis, condition monitoring or process optimization. As the development of Digital Twins is a highly interdisciplinary task, it poses challenges and is therefore rarely utilized. This contribution considers the interdisciplinary development of Digital Twins as an interplay between sensors, models and IT infrastructure. It builds on previous publications that deal with the domains of models, sensors and IT infrastructures in the context of Digital Twins as well as domain-specific development procedures. For this purpose, the V‑model of VDI 2206 is used and modified for the context of the Digital Twin. In order to integrate the findings of the preliminary work into the V‑model at a more concrete level, they are sorted into an RFLP framework, which in turn is integrated into the V‑model. The resulting development approach covers the entire development process at a transferable, abstract level, while at the same time providing concrete steps at a directly applicable level. The results are illustrated using an exemplary application of an industrial gearbox.
CRIS-Team Scopus Importer:2025-03-14